Comparative Framing Analysis: BBC News Arabic versus AlHadath on Assad’s Fall - Fadhilah, Nadia Sailil; Al Anshory, Abdul Muntaqim (Journalism Study Program, Faculty of Communication Sciences, Universitas Padjadjaran, 2026)
Background: The fall of Bashar al-Assad’s regime in Syria has prompted various national and international media outlets to reveal how they, with different geopolitical positions, construct contrasting narratives despite covering the same events. Purpose: This research reveals how two international online media outlets with different geopolitical backgrounds, BBC News Arabic and AlHadath, frame the issue in response to key figures who were fully involved in the fall of Bashar al-Assad’s regime. Methods: This study used Robert N. Entman’s framing analysis model, which comprises four elements: defining problems; diagnosing causes, making moral judgment; and treatment recommendations. Data collection was conducted using observation and note-taking techniques, with primary data from two news videos: “Assad Speaks for the First Time after His Fall” from BBC News Arabic and “President of the Syrian National Coalition: I Announce the Fall of Bashar Al-Assad’s Regime” from AlHadath. The secondary data consisted of scientific articles, journals, and books. Results: The study shows that BBC News Arabic defines the problem as political instability caused by an endless civil war and external political pressure. Thus, this media outlet remains neutral by emphasizing diplomatic adjustments. Meanwhile, AlHadath defines the problem as the fall of a dictatorial regime that oppresses the people and civilians due to popular resistance. Clearly, this media outlet criticizes the Assad regime and advocates for a transition of power to the opposition. Conclusion: These findings explain how the media works to reveal fundamental domination and institutional bias. The difference between these two frames shows the ideological situation and geopolitical objectives of the two media outlets. Implications: This study shows that framing in the media is a strategic tool designed to sway public opinion in the interest of political legitimacy.